2020
DOI: 10.1088/1361-6641/aba08e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tellurium and silicon as n-type dopants for GaAsBi

Abstract: Films of n-GaAs1-xBix films were grown via molecular beam epitaxy using both Si and Te as dopant sources. Electron mobility was characterized by Hall effect measurements as a function of carrier concentration and Bi content for films with bismuth fractions of x = 0.02 and x = 0.06. While GaAsBi:Te shows lower majority carrier mobility than GaAsBi:Si at low Bi concentrations, the two become comparable as Bi content increases. Furthermore, it was observed that in the presence of bi-metallic Bi-Ga droplets on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that an intrinsic 1.0 eV GaAsBi (~ 5.5% Bi) is slightly p -type with a carrier density of 1 × 10 15 –1 × 10 16 cm −3 [ 32 ]. Although it is possible to dope GaAsBi either p - or n -type, which could potentially improve the subcell’s V oc , there is a risk that already low carrier lifetimes in the bismide will decrease even further [ 26 , 33 ]. To stay on the safe side, we used an intrinsic GaAsBi.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that an intrinsic 1.0 eV GaAsBi (~ 5.5% Bi) is slightly p -type with a carrier density of 1 × 10 15 –1 × 10 16 cm −3 [ 32 ]. Although it is possible to dope GaAsBi either p - or n -type, which could potentially improve the subcell’s V oc , there is a risk that already low carrier lifetimes in the bismide will decrease even further [ 26 , 33 ]. To stay on the safe side, we used an intrinsic GaAsBi.…”
Section: Resultsmentioning
confidence: 99%
“…For electrical characterization of these devices, all samples have been fabricated in form of circular mesas. Ge/Au/Ni/Au Ohmic contacts were thermally evaporated on the back side of the wafer, with thickness (10,20,20 and 150) nm, respectively. Then rapid thermal annealing (RTA) in an Ar atmosphere was performed at 380℃ for 30 seconds.…”
Section: -Experimental Detailsmentioning
confidence: 99%
“…(100) GaAs(1−x)Bix [7,10,11,[17][18][19][20]. Therefore, it is worth noting that the structural and optical properties of n-type GaAs(1−x)Bix alloys and devices using non-(100) GaAs substrates have not been investigated yet.…”
mentioning
confidence: 99%
“…As pointed previously, there are few studies on optical and electrical properties of nand p-doped GaAs(1−x)Bix alloys [14][15][16][17][18][19][20][21]. Particularly, it was shown that the incorporation of Bi suppresses the formation of GaAs-like electron traps, thus reducing the total trap concentration in dilute GaAs(1−x)Bix layers as compared to GaAs grown under the same growth conditions [18].…”
Section: Photoluminescencementioning
confidence: 99%
“…Remarkably, it has been shown that enhancement of Bi incorporation in GaAs (1−x) Bi x thin films could be obtained by using (311)B orientation [9]. On the other hand, while optoelectronic devices require a controllable methodology for the doping of alloys, there are relatively a very few studies addressing the doping process of only (100) GaAs (1−x) Bi x [14][15][16][17][18][19][20][21]. These investigations have particularly concentrated on the effects the doping has on the structural, electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%